2022
DOI: 10.1021/acs.organomet.2c00427
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of a Superbulky Low-Valent β-Diketiminate Al(I) Complex

Abstract: Low-valent β-diketiminate Al­(I) complexes are generally synthesized in low yields (<20%). This is due to an intermolecular decomposition reaction. A new β-diketiminate Al­(I) complex with a very bulky β-diketiminate ligand DIPePBDI was obtained in a high yield (81%) and the raw product was found to be essentially pure (DIPePBDI = HC­[C­(Me)­N­(DIPeP)]2; DIPeP = 2,6-C­(H)­Et2-phenyl). The crystal structure of (DIPePBDI)­Al shows a monomeric complex. The reaction of (DIPePBDI)­Al with AlBr3 gave (DIPePBDI)­AlBr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
(82 reference statements)
0
16
0
Order By: Relevance
“…However, after performing the reaction just above the melting point of the solvent (10 °C) and removal of benzene by freeze‐drying at −15 °C, [( DIPeP BDI)Sr] 2 (C 6 H 6 ) ( 4 ) could be extracted with cold pentane in form of an essentially pure pitch‐black powder (61 % yield). We anticipate that this recently introduced benzene freeze‐drying method [25] could generally become a key to the isolation of thermally labile complexes. Crystallization from pentane gave black crystals of 4 which are even at −20 °C only of limited stability.…”
Section: Methodsmentioning
confidence: 99%
“…However, after performing the reaction just above the melting point of the solvent (10 °C) and removal of benzene by freeze‐drying at −15 °C, [( DIPeP BDI)Sr] 2 (C 6 H 6 ) ( 4 ) could be extracted with cold pentane in form of an essentially pure pitch‐black powder (61 % yield). We anticipate that this recently introduced benzene freeze‐drying method [25] could generally become a key to the isolation of thermally labile complexes. Crystallization from pentane gave black crystals of 4 which are even at −20 °C only of limited stability.…”
Section: Methodsmentioning
confidence: 99%
“…An analogous reaction of the NDipep substituted precursor Al(BDI Dipep ) ( VII ) with K[R] was shown to be solvent dependant. 12 In hexane the reaction forms exclusively the potassium aluminyl [K{Al(BDI Dipep -H)}] 2 4 Dipep , whereas in benzene a mixture of 4 Dipep and a ligand C–H activation product was formed.…”
Section: Synthesis and Structures Of Aluminylsmentioning
confidence: 99%
“…X-Ray crystallography has shown that the potassium aluminyls 1 , 28 2 , 29 3 Ar (Ar = Dipp, 30 Mes 31 ) and 4 Ar (Ar = Dipp, 32 Dipep 12 ) exist as contacted dimeric pairs (CDPs) in the solid-state, in which the two aluminyl anions are linked by flanking K⋯π(arene) interactions (Fig. 3).…”
Section: Synthesis and Structures Of Aluminylsmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit the seminal work of Aldridge and Goicoechea first reported the activation of the H–H bond in benzene, the dual activation of C–H bonds in para positions was first reported by Harder et al using catalyst VI bearing an N,N ligand . Other seminal examples and reactivity regarding aluminyl anions can be found in the literature and references therein.…”
Section: Introductionmentioning
confidence: 99%